THE RELATIONSHIP BETWEEN DIGITAL LITERACY AND DIGITAL MARKETING CREATIVITY IN STUDENTS AT SMK MASTER INDONESIA - Murdiyono Murdiyono; Didi Sukardi; Rahmatullah Rahmatullah; I Nyoman Suri Adnyana (Yayasan Nusantara Hasana Berdikari, 2023)
This study aims to analyze the relationship between digital literacy and digital marketing creativity among students at SMK Master Indonesia. Digital literacy is a crucial skill for students in effectively utilizing information technology and social media for digital marketing activities. The research method used a quantitative approach by distributing questionnaires to SMK Master Indonesia students as research respondents. The results showed that digital literacy has a positive relationship with students' digital marketing creativity, particularly in the ability to create promotional content, use social media, and digital technology-based marketing innovation